Smart window by thin film wrinkling - Leong, Alicia Fong Ting (2017)
Smart windows with switchable light transmittance properties have been used to improve the ambience, keeping heat out and ultimately to save energy. People usually spend 80 to 90% of their time indoors. When people stay indoor in the day, it is desirable to achieve a suitable room temperature without turning on the air-conditioner. Given that Singapore has been getting warmer and the temperature is reportedly to be getting higher, the smart window could hence help us to get the desired temperature and block the ultraviolet (UV) rays. Good performance in energy saving can also bring along financial benefits. A study has shown that “green” buildings can get higher rental and selling rates. Furthermore, this allows privacy in commercial uses or home purposes, and can be easily achieved via the use of just a switch, or even through the use of light rays transmission, electrical voltage and temperature. Surface wrinkling of elastomer has been widely researched on due to its low cost and promising results. Many of the research revolves around the different type of transparent conductive oxides coating on the elastomers to determine the amount of light transmission